2022
DOI: 10.1186/s13075-021-02695-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained low disease activity measured by ASDAS slow radiographic spinal progression in axial spondyloarthritis patients treated with TNF-inhibitors: data from REGISPONSERBIO

Abstract: Background To evaluate the influence of the disease activity on radiographic progression in axial spondyloarthritis (axSpA) patients treated with TNF inhibitors (TNFi). Methods The study included 101 axSpA patients from the Spanish Register of Biological Therapy in Spondyloarthritides (REGISPONSERBIO), which had clinical data and radiographic assessment available. Patients were classified into 2 groups based on the duration of TNFi treatment at bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The normal section is given a value of 0. If erosion, sclerosis, or squaring is found, it is given a value of 1, the presence of syndesmophyte is given a value of 2, and the presence of complete bridging is given a value of 3 with a value range of 0–72 [ 8 , 17 ]. Measuring the mSASSS score was carried out based on lumbosacral and cervical radiology with two rheumatologists with inter-observer assessment (Kappa test = 86%) [ 8 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The normal section is given a value of 0. If erosion, sclerosis, or squaring is found, it is given a value of 1, the presence of syndesmophyte is given a value of 2, and the presence of complete bridging is given a value of 3 with a value range of 0–72 [ 8 , 17 ]. Measuring the mSASSS score was carried out based on lumbosacral and cervical radiology with two rheumatologists with inter-observer assessment (Kappa test = 86%) [ 8 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies do not give a conclusive answer, as there are methodological issues in several of these studies [37]. Interestingly, it was confirmed that reduction in structural progression was mediated by reduction in ASDAS [15,17,38].…”
Section: Tnfimentioning
confidence: 98%
“…In addition, both inflammatory and structural lesions in the axial skeleton are associated with decreased functional status and restricted spinal mobility, affecting daily activities of patients with axSpA [12,13]. Moreover, literature showed that disease activity measured by Axial Spondyloarthritis Disease Activity Score (ASDAS), but not by Bath Ankylosing Spondylitis Disease Activity Index or C reactive protein alone, is longitudinally associated with progression of radiographic spinal progression [14][15][16][17]. Naturally disease-modifying interventions in axSpA concentrate on preventing deterioration in the factors associated with this structural progression paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while some studies suggest the existence of a coupling between inflammation-and disease activity-and new bone formation in patients with AS [196][197][198], others demonstrate that ossification progresses independently from the suppression of inflammation involving adjacent but distinct sites [199,200]. Moreover, most findings from clinical trials show less bone formation in patients with axSpA treated with bDMARDs whose disease is well controlled by the therapy, suggesting that new bone formation in the context of a clinically controlled disease could be explained by a subclinical, persistent, non-detectable joint inflammation [201,202].…”
Section: New Bone Formation In Spondyloarthritismentioning
confidence: 99%